2016
DOI: 10.3168/jds.2015-10837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet supplementation with Ascophyllum nodosum on cow milk composition and microbiota

Abstract: Iodine deficiency remains a major public health concern in many countries, including some European regions. This study aimed at understanding the effect of a supplement of marine alga Ascophyllum nodosum as a iodine fortifier in the cow diet, on the compositional and microbiological quality of milk. The results obtained in this work indicated that the dietary inclusion of A. nodosum exerted significant effects on cow milk composition. In particular, it increased iodine content and reduced the quantity of free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
(54 reference statements)
3
17
1
1
Order By: Relevance
“…Results and taxonomic classification are presented in Figure 1 The number of studies carried out in milk water buffalo is too limited to identify a common healthy and unhealthy microbiota. In bovine milk, beside those related to inflammation (Oikonomou et al, 2014;Catozzi et al, 2017;Lima et al, 2017), variations in milk microbiota have been linked not only to antibiotic treatment (Ganda et al, 2016(Ganda et al, , 2017, as expected, but also to lactation stage, weather conditions, and diet supplementation (Chaves Lopez et al, 2016;Li et al, 2018), suggesting the presence of a wide range of factors and sources influencing the milk microbial community (Derakhshani et al, 2018). Therefore, possible variations of the relative abundance at phyla and family levels found in this study as compared with previous ones could be related to different management conditions.…”
Section: Short Communicationmentioning
confidence: 86%
“…Results and taxonomic classification are presented in Figure 1 The number of studies carried out in milk water buffalo is too limited to identify a common healthy and unhealthy microbiota. In bovine milk, beside those related to inflammation (Oikonomou et al, 2014;Catozzi et al, 2017;Lima et al, 2017), variations in milk microbiota have been linked not only to antibiotic treatment (Ganda et al, 2016(Ganda et al, , 2017, as expected, but also to lactation stage, weather conditions, and diet supplementation (Chaves Lopez et al, 2016;Li et al, 2018), suggesting the presence of a wide range of factors and sources influencing the milk microbial community (Derakhshani et al, 2018). Therefore, possible variations of the relative abundance at phyla and family levels found in this study as compared with previous ones could be related to different management conditions.…”
Section: Short Communicationmentioning
confidence: 86%
“…Most studies on milk microbiota have used mature milk, but few have investigated colostrum microbiota in human and bovines (Aakko et al, 2017;Lima et al, 2017;Toscano et al, 2017;Derakhshani et al, 2018c). Some studies considered milk collected from only one nipple or teat, whereas others considered pooled milk (Dolci et al, 2014;Chaves Lopez et al, 2016). Bacteria have been shown to be present in milk in a free-living, "planktonic" state, but they can also be associated with immune cells.…”
Section: Milk Microbiota: Current Studies and Limitsmentioning
confidence: 99%
“…Antaya et al (2015) reported linear increases in the concentration (from 178 to 1,370 µg/L) and yield (from 2.82 to 20.6 mg/d) of milk I in dairy cows supplemented with incremental amounts of KM, due to elevated I intake. Chaves Lopez et al (2016) demonstrated a 113% increase in milk I concentration with feeding (% of the diet DM) 2.3% of KM incorporated in a ground corn-based concentrate blend. In contrast, Sorge et al (2016b) reported no effect of KM supplementation (56 g/d) on milk I concentration.…”
Section: Iodine Metabolism and Glucosinolates Intakementioning
confidence: 99%